Printable Transparent Microelectrodes toward Mechanically and Visually Imperceptible Electronics. (12th August 2020) - Takemoto, Ashuya; Araki, Teppei; Uemura, Takafumi; Noda, Yuki; Yoshimoto, Shusuke; Izumi, Shintaro; Tsuruta, Shuichi; Sekitani, Tsuyoshi
Abstract : Flexible and transparent electrodes are highly useful in wearable optoelectronic systems for healthcare and biosensing applications for conducting multimodal assessments with electrophysiological and optical measures. In such systems, the electrodes should exhibit a low sheet resistance, high visible transmittance, and small feature size, for reliable electrical sensing, optical observation of attached objects, and integration of devices for mapping local biology events, respectively. Herein, fine‐printed, flexible, and transparent microelectrodes that allow biosensing and device integration are reported. The microelectrodes containing cross‐aligned silver nanowire (AgNW) networks are patterned via a selective wetting deposition technique on a 1 μm‐thick polymer substrate. A low sheet resistance of 25 Ω sq −1 and a visible transmittance of 96%–99% are achieved with a small pattern width of 25 μm. The biosensing application is demonstrated by detecting the leaf electric potential; the leaf cells under the microelectrodes are observed because of visible transparency. Furthermore, device integration is demonstrated by electronic circuits with ultrathin and transparent organic transistors. The transistors exhibit white‐light illumination stability and mechanical stability to bending stress. These demonstrations provide a basis for developing ultraimperceptible wearable sensor systems with ultrathinness and high visible transmittance. Abstract : Fine‐printed, flexible, and transparent microelectrodes are developed for future optoelectronic sensor systems. The microelectrodes exhibit a low sheet resistance (25 Ω sq −1 ), high visible transmittance (96%–99%), and small feature size (25 μm). They are utilized to acquire the biopotential of a leaf and are applied in organic circuits. The results provide a basis for ultraimperceptible wearable sensor systems.